2004
DOI: 10.1111/j.1432-2277.2004.tb00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancy after organ transplantation: a retrospective survey in Italy

Abstract: The number of women who decide to have a child after organ transplantation has increased. We determined the outcomes of 67 pregnancies of women who had undergone kidney, liver or heart transplantation. All recipients had been maintained on immunosuppressive therapy before and during pregnancy. Pregnancy complications at term were observed in 17 out of 67 women (25%), hypertension being the most frequent complication (16.17%). Two transplant rejections were reported. Sixty‐eight infants were delivered (includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(28 reference statements)
0
3
0
2
Order By: Relevance
“…Among the 638 citations that were initially retrieved from the 3 electronic database searches, 578 were found to be unique studies that qualified for abstract screening. After the screening, 18 full‐text articles were reviewed, of which 10 were excluded: 1 article that specifically studied the teratogenic effects of mycophenolate mofetil in 3 LT recipients and the effects of sirolimus in 2 LT recipients,17 2 review articles,18, 19 3 studies of multiorgan transplant recipients,20‐22 4 studies that did not involve post‐LT pregnancy outcomes,2, 23‐25 and 1 study of a duplicate/identical cohort 1. Ultimately, 8 studies were selected for inclusion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 638 citations that were initially retrieved from the 3 electronic database searches, 578 were found to be unique studies that qualified for abstract screening. After the screening, 18 full‐text articles were reviewed, of which 10 were excluded: 1 article that specifically studied the teratogenic effects of mycophenolate mofetil in 3 LT recipients and the effects of sirolimus in 2 LT recipients,17 2 review articles,18, 19 3 studies of multiorgan transplant recipients,20‐22 4 studies that did not involve post‐LT pregnancy outcomes,2, 23‐25 and 1 study of a duplicate/identical cohort 1. Ultimately, 8 studies were selected for inclusion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Leur métabolite actif traverse le placenta avec une concentration foetale correspondant au dixième de la concentration maternelle avec un risque de 5 % d'insuffisance surrénalienne même à doses faibles [28,29]. Nous pensons, néanmoins, qu'il est nécessaire d'organiser une surveillance de ces nouveau-nés exposés in utero aux traitements immunosuppresseurs afin de déceler l'apparition d'é-ventuelles complications de ces traitements [26][27][28][29][30][31].…”
Section: Discussionunclassified
“…Using GPI-1046, it was shown that FKBP52 activity was required for growth cone guidance, but not for general axon growth. The authors raised concern that the use of FK506 and other IL may therefore disturb fetal nervous system development [137] but acknowledge that the use of specific inhibitors may have therapeutic relevance.…”
Section: Fkbp52mentioning
confidence: 98%